Investigation on the effect of external mechanical stress on the DC characteristics of GaAs microwave devices. Issue 9 (August 2015) - Adokanou, K.; Inal, K.; Montmitonnet, P.; Pressecq, F.; Bonnet, B.; Muraro, J.-L.
Abstract: Stress control is a main factor in the operation, performance and reliability of GaAs devices. A precise understanding of the impact of the mechanical stress on the performance and reliability of GaAs devices can lead to the improvement of the device design and packaging. Most of the time, process flow parameter modifications help to change internal stress in multilayer properties and this has a direct impact on the electric parameters. Mechanical wafer bending is the method usually used to investigate the effects of external stress on Gallium Arsenide (GaAs) devices. The aim of this work is to quantify the sensibility of GaAs microwave devices used for Space applications under mechanical external stress in order to estimate the impact of packaging. In this innovative work, a bending-by-buckling system has been used to apply external mechanical stress on a single GaAs microwave die. To evaluate the value of this stress in device structure and precisely near the channel of the pseudomorphic High Electron Mobility Transistor (pHEMT), simulation based on the Finite Element Method has been carried out. The stress was increased gradually from 0 to 210 MPa (in tension and compression) and then reduced from 210 MPa to 0. The experimental results demonstrate that the threshold current changes linearly and reversibly in the range of the applied stress. The shift in the threshold current and voltage of the pHEMT was analysed by considering piezoelectric effects. Graphical abstract: Highlights: Study of mechanical stress influence on GaAs transistor DC characteristics Simple bending system by buckling, easily portable under characterization systems Mechanical external stress has been applied from -210 MPa to 210 MPa and has been evaluated with Abaqus standard ® Step up measurement has been calibrated with and without applied stress Threshold voltage and current are given as functions of applied mechanical stress